DESIGN AND DEVELOPMENTOF DUAL-STATOR RADIAL-FLUX PERMANENT MAGNET MACHINE FOR CEILING FAN APPLICATION - ZULKARNAIN, NUR FARAHIN (2018)
Ceiling fan is classified as an important electrical appliance for cooling purpose in tropical countries, significantly in Malaysia. However, the conventional ceiling fan has only 30 % of overall efficiency and low in performance. Hence, the main purpose of this research is to develop a ceiling fan motor that is high in efficiency and less power consumption by implementing a concept of dual-stator that comprises the motor and the generator in one system.